The Effects Of Visual Signalling Principle In A Desktop Virtual Reality Based Learning Environment On Students’ Performance, Cognitive Load And Perceived Motivation - Wong, Ai Chin (2018)
The purpose of this study was to investigate the effect of learning science laboratory safety using visual signalling principle in a virtual reality environment on students’ performance, cognitive load and perceived motivation among students with different spatial ability. A 22 quasi experimental factorial design was adopted in this research. The independent variables used in the learning of science laboratory safety were the two modes of courseware which is virtual reality with signalling (VRS) and virtual reality with non-signalling (VRNS). The moderator variable was the spatial ability.